Lingkar pinggang dan lingkar leher dengan kadar kolesterol total pada wanita usia subur obesitas - Rifial Ramadhan Manik; Nurmasari Widyastuti; Choirun Nissa (Jurnal Gizi Klinik Indonesia, 2019)
Waist circumference, and neck circumference correlated to total cholesterol among reproductive-age women with obesityBackground: Dyslipidemia is a metabolic disorder condition that is closely related to cholesterol and obesity. The prevalence of obesity in reproductive-age women (>18 years) in Indonesia increased dramatically. Reproductive age women with obesity are at greater risk of hypercholesterolemia compared with non-obese. Waist circumference (WC), mid-upper arm circumference (MUAC), and neck circumference (NC) can be used as a marker of higher or low cholesterol levels. Objective: This study aimed to determine the relationship between WC, MUAC, and NC with total cholesterol. Methods: The study design was cross-sectional with several subjects were 54 women of reproductive-aged 18-29 years. Subject with obese category (BMI ≥25kg/m2) was measured the WC, MUA, and NC as an independent variable and total cholesterol as the dependent variable, and dietary intake (total fat, cholesterol, and saturated fat) as confounding variables. The bivariate analysis used the Pearson correlation test. Multivariate analysis used multivariate linear regression. Results: Bivariate analysis showed there was a significant relationship between WC and NC to total cholesterol (p=0.006 and p=0.001), but not on MUAC (p=0.063). In multivariate analysis, NC is the most significantly related to total cholesterol (β=0.367; p=0.004; Adjusted R Square 24%) than WC. Conclusions: There is a significant relationship between WC and NC to the total cholesterol in women of reproductive age obesity. NC more significantly related to total cholesterol.